Organizing long-term follow-up care for pediatric cancer survivors: a socio-ecological approach - Aleshchenko, Ekaterina; Langer, Thorsten; Calaminus, Gabriele; Gebauer, Judith; Swart, Enno; Baust, Katja (Frontiers in public health, 2025)
This study examines the organization of long-term follow-up care for pediatric cancer survivors through the lens of Bronfenbrenners’ Ecological Systems Theory (EST). Using focus group discussions with survivors and healthcare professionals across Germany, we aimed to identify challenges and facilitators in care provision. Data were gathered during four focus groups, each consisting of 5–9 participants. A multimethods approach was used, employing both inductive and deductive thematic analysis. Results indicated key challenges such as fragmented care during transitions and insufficient offer of psychological support. The application of EST revealed the importance of coordinating care across multiple system levels: microsystem (direct care), mesosystem (coordination between care settings), exosystem (healthcare policies), and macrosystem (cultural attitudes). The study proposes strategies to improve care, such as implementing case managers and introducing culturally sensible long-term follow-up protocols. These findings highlight the complexity of survivorship care and the need for a more integrated approach to meet the evolving needs of survivors after childhood and adolescent cancer.